Penerapan E-Supply Chain Management Pada Industri (Studi Kasus Pada PT Maitland-Smith Indonesia) - Enty Nur Hayati; Mumpuni Wijiasih Fitriyah (Jurnal Ilmiah Dinamika Teknik, 2015)
Is management of various activities in order to obtain raw materials, continued transformation activities so that it becomes a product in the process, and then be forwarded to the finished product and delivery to consumers through the distribution system. E-SCM is a management concept, the company leverages Internet technology and the existing network to integrate all business partners of the company (relating to the supply of materials, production processes and delivery of goods), mainly related to system suppliers of raw materials or resources needed in the production process. PT Maitland-Smith Indonesia is one company in Indonesia, the furniture sector involving many parties in the production process and requires the existence of a stream of material / product as well as good information. Therefore PT Maitland-Smith uses e-SCM to help integrate all business partners of the company. To achieve information sharing in the supply chain in PT Maitland-Smith Indonesia, it needed a technology that is enterprise resources planning (ERP) System. ERP software used by PT Maitland-Smith Indonesia is QAD Enterprise Cloud. Keywords: SCM, E-SCM, ERP